Effectiveness of the Fungal Metabolite 3-O-Methylfunicone towards Canine Coronavirus in a Canine Fibrosarcoma Cell Line (A72) - Claudia Cerracchio; Valentina Iovane; Maria Michela Salvatore; Maria Grazia Amoroso; Hiba Dakroub; Marina DellaGreca; Rosario Nicoletti; Anna Andolfi; Filomena Fiorito (MDPI AG, 2022)
Canine coronavirus (CCoV), an alphacoronavirus, may cause self-limiting enteric disease in dogs, especially in puppies. The noteworthy plasticity of coronaviruses (CoVs) occurs through mutation and recombination processes, which sometimes generate new dangerous variants. The ongoing SARS-CoV-2 pandemic and the isolation of a novel canine-feline recombinant alphacoronavirus from humans emphasizes the cross-species transmission ability of CoVs. In this context, exploring antiviral compounds is essential to find new tools for fighting against CoVs infections. Fungi produce secondary metabolites, which are often developed as antibiotics, fungicides, hormones, and plant growth regulators. Previous examinations of benzo-γ-pyrone 3-O-methylfunicone (OMF), obtained from Talaromyces pinophilus, showed that it reduces the infectivity of hepatitis C virus and bovine herpesvirus 1. Based on this evidence, this study evaluated the antiviral ability of OMF against CCoV infection in a canine fibrosarcoma (A72) cell line. During CCoV infection, a non-toxic dose of OMF markedly increased features of cell viability. Moreover, OMF induced a significant reduction in virus yield in the presence of an intense downregulation of the viral nucleocapsid protein (NP). These findings occurred in the presence of a marked reduction in the aryl hydrocarbon receptor (AhR) expression. Taken together, preliminary findings suggest that OMF inhibiting AhR shows promising activity against CCoV infection.